"r/Thritis", Pregnancy, and Parenting: A Qualitative Descriptive Study of Reddit Forums to Explore Information Needs and Concerns of Women With Rheumatoid Arthritis. Issue 8 (15th August 2019) - Chew, Caitlin; Rebić, Nevena; Baldwin, Corisande; Amiri, Neda; Proulx, Laurie; De Vera, Mary A.
Abstract : Objective: Rheumatoid arthritis (RA) disproportionately affects more women than men, often striking during childbearing years. Because the Internet, particularly social media, is increasingly used by patients with chronic conditions seeking and sharing information, our objective was to conduct a qualitative descriptive study of threads on the social news website, Reddit, to understand the information needs and concerns of women with RA regarding pregnancy and parenting. Methods: We searched threads (original posts and responses) on three subreddit sites, "r/Thritis, " "r/Rheumatoid, " and "r/BabyBumps, " over a 10‐year period between October 27, 2008, and October 27, 2018. All threads were reviewed, and those that specifically mentioned having RA and fertility/family planning, pregnancy/reproduction, and/or parenting/having children were included. We applied a thematic analysis to the threads, which involved initial line‐by‐line coding, clustering of codes into subcategories and categories, and abstraction into final themes. Results: We identified 87 threads and included 59 for qualitative analysis. The thematic analysis led to the identification of five themes. Theme one (finding a community) captures motivations for seeking information online. Themes two (making decisions about pregnancy and having children) and three (worrying about the impacts of arthritis on pregnancy and parenting) capture women's concerns and thought processes. Themes four (information needs for managing arthritis throughout the perinatal period) and five (pregnancy information and resources for women with arthritis) describe the community's specific informational needs. Conclusion: A qualitative analysis of publicly available threads about the relationship between RA and issues of pregnancy and parenting identified areas of concern and further information need. These forums also provided an online community where women with RA sought social support and encouragement. Altogether, findings speak to the importance of supporting the information and care needs of women with RA who are pregnant or considering pregnancy.